Greener marketing - Grant, John (Wiley, 2020)
***BUSINESS BOOK AWARDS - FINALIST 2021*** This timely book is a sequel to John Grant's Green Marketing Manifesto (2007) the award-winning and bestselling definitive guide to green marketing (and not greenwashing). Fast forward to mid-2020. Climate Change is back at the top of the public and political agenda. Even after covid-19, hundreds of big-name CEOs are committing to a #greenrecovery. And surveys show widespread global public support for this and recent shifts in sustainable behaviours and attitudes in markets ranging from organic food to flying. Sustainable brands are significantly outperforming conventional ones. As are sustainability related stock prices. Companies like Unilever continue to set ambitious targets related not just to climate, but biodiversity and deforestation, plastics, social justice, regenerative farming. Sustainability related trends such as plant-based foods and electric vehicles are showing steep growth and creating tomorrow's superbrands (Impossible, TESLA...). This book is packed with up to date learnings, case examples and trends, covering everything from eco labelling, transparency and the circular economy; to rebound effects, sustainable finance, blockchain and regenerative farming. A core message being that to drive sustainability, marketers firstly do really need to properly understand sustainability, its many applications and implications. Secondly to be effective, marketers need to understand what it means to their consumers and other significant audiences. Hence the book takes a long hard look at what was driving all the protests, boycotts and petitions in 2019 and what ideas, causes and platforms caught the public imagination. The ultimate goal is to go beyond marketing that simply looks good, to marketing that does good. This book helps in achieving that goal by showing the reader how to: * Uncover strategies for sustainable marketing that actually deliver on green and social objectives, not just greenwashing * Reconceptualise marketing and business models, and learn to recognise the commercial strategies and approaches that are no longer fit for purpose * Learn how hot topics like the climate crisis, biodiversity, social justice, single use plastics and supply chain transparency influence green and social marketing * Read about numerous examples and case studies from both brand leaders and challengers that have developed innovations and fresh creative approaches to green and social marketing * Get practical tools, models, facts, strategies, workshop and project processes and business case rationales - so that you can build your own plans and proposals This book is intended to assist marketers, by means of clear and practical guidance, through a complex transition towards meaningful marketing that makes a positive creative impact on the climate crisis and on improving human life in troubled times. Aimed both at big companies that are trying to be good, and good companies that are trying to be big.